The Oversight Role Of Legislative Institutions In Emergency Situations (Comparison Of Indonesia With The United States) - Putri, Rizqya Nafila; Ausath, Muhammad Ali (Constitutionale, 2024)
An emergency situation disrupts the normal functioning of a country, rendering standard laws and procedures ineffective. In such cases, extraordinary measures are required, and the President, as the executive authority, is granted significant powers to address the emergency. The House of Representatives (DPR), as the legislative body, is responsible for overseeing the executive branch. However, the oversight function of the DPR appears to be suspended during emergencies under Government Regulation in Lieu of Law Number 23 of 1959 (Perppu Keadaan Darurat). Furthermore, there are no clear guidelines defining the DPR's role during states of emergency in Indonesia. The DPR's oversight function is crucial and cannot be eliminated, as it represents the people's interests and voices. This article employs a normative juridical method, incorporating conceptual, comparative, and legislative approaches with a descriptive analysis. It aims to explore the role of legislative oversight in emergency situations in both Indonesia and the United States, comparing the effectiveness of their oversight systems in preventing power abuse and protecting human rights. The United States has established regulations to ensure legislative oversight during emergencies, thereby preventing arbitrary actions by the executive. Indonesia could benefit from adopting similar mechanisms to enhance its legislative oversight during emergencies and better protect human rights.